2017
DOI: 10.1111/jopy.12327
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in personality change across the adult life span

Abstract: These results inform theories of life span development and provide future directions for research on the causes and conditions of personality change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
91
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 152 publications
(113 citation statements)
references
References 65 publications
8
91
0
1
Order By: Relevance
“…The TOSCA sample consists of students in young adulthood, a critical period in personality development marked by confluence of multiple developmental tasks (Arnett, 2000) and dramatic increase in multiple personality traits in putatively positive directions (Roberts, Walton & Viechtbauer, 2006). However, given that other age groups have shown differential change trajectories of personality traits (Roberts, Walton & Viechtbauer, 2006;Schwaba & Bleidorn, 2018) and depression (Hankin et al, 1998), the associations observed among neuroticism, self-esteem and depression could be affected by developmental challenges specific to other age groups. Future research should examine the associations among self-esteem, depression and neuroticism as well as their continuity and change in other life stages, such as adolescence or senior adulthood.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…The TOSCA sample consists of students in young adulthood, a critical period in personality development marked by confluence of multiple developmental tasks (Arnett, 2000) and dramatic increase in multiple personality traits in putatively positive directions (Roberts, Walton & Viechtbauer, 2006). However, given that other age groups have shown differential change trajectories of personality traits (Roberts, Walton & Viechtbauer, 2006;Schwaba & Bleidorn, 2018) and depression (Hankin et al, 1998), the associations observed among neuroticism, self-esteem and depression could be affected by developmental challenges specific to other age groups. Future research should examine the associations among self-esteem, depression and neuroticism as well as their continuity and change in other life stages, such as adolescence or senior adulthood.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Broad personality traits are powerful predictors of various central life outcomes (e.g., Costa, McCrae, & Löckenhoff, 2019; Ozer & Benet‐Martínez, 2006; Soto, 2019). Given the importance of personality traits for both individual and society, a natural question to consider is how personality traits develop across the lifespan (Schwaba & Bleidorn, 2017). Recent years have witnessed rising interest in adult personality development (Specht et al, 2014) and accumulating empirical evidence for continuous personality plasticity, showing that personality traits can and do change at any time across the lifespan (Roberts, Walton, & Viechtbauer, 2006; Roberts, Wood, & Caspi, 2008; Specht et al, 2014; Wrzus & Roberts, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…We also found individual differences in ipsative or profile DEVELOPMENT OF SELF-CONCEPT 22 consistency where some people used the same categories in their self-concept over time, and other people tended to reconfigure their self-concept. For personality traits, there are relatively modest amounts of individual differences in mean-level as well as ipsative change, especially at older ages, with most individual differences in personality trait change occurring in young adulthood (Donnellan et al, 2007;Robins, Fraley, Roberts, & Trzesniewski, 2001;Oltmanns, Jackson & Oltmanns, 2018;Schwaba & Bleidorn, 2018). Self-concept development, in contrast, appears to be quite idiosyncratic, with some people showing no consistency whereas others show perfect consistency.…”
Section: Development Of Self-concept 21mentioning
confidence: 99%